A Simple Survey of the Preparation Situation for Resident's Evacuation in Japanese Prefectures After the Fukushima Daiichi Nuclear Power Plant Accident - Takakiyo Tsujiguchi; Takakiyo Tsujiguchi; Mizuki Sakamoto; Tomoki Koiwa; Yoko Suzuki; Kouya Ogura; Kouya Ogura; Katsuhiro Ito; Kanako Yamanouchi; Ikuo Kashiwakura; Ikuo Kashiwakura (Frontiers Media S.A., 2020)
The Japanese government formulated the Nuclear Emergency Response Guidelines in response to the Fukushima Daiichi Nuclear Power Plant accident (FDNPP accident) caused by the Great East Japan Earthquake in March 2011. Under these guidelines, Japan has established its current nuclear disaster response system. This manuscript outlines the transition of Japan's nuclear disaster response system before and after the FDNPP accident and also shows the results of a questionnaire survey on the level of preparation the prefecture currently has for the evacuation of residents at the time of a nuclear disaster. About 70% of the prefectures where nuclear facilities are located or adjacent have completed or are in the process of completing evacuation plans, and all except one indicated they have the equipment needed to perform radiation contamination inspections of residents. These results suggest that activities are taking place throughout Japan to build a new disaster response system. It will be important to verify whether the evacuation manuals prepared by prefectural governments are effective through large-scale training and to develop human resources for performing radiation contamination inspections of evacuating residents.